2017
DOI: 10.1186/s13148-017-0329-3
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic signatures of gestational diabetes mellitus on cord blood methylation

Abstract: BackgroundIntrauterine exposure to gestational diabetes mellitus (GDM) confers a lifelong increased risk for metabolic and other complex disorders to the offspring. GDM-induced epigenetic modifications modulating gene regulation and persisting into later life are generally assumed to mediate these elevated disease susceptibilities. To identify candidate genes for fetal programming, we compared genome-wide methylation patterns of fetal cord bloods (FCBs) from GDM and control pregnancies.Methods and resultsUsing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
96
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 62 publications
(71 reference statements)
4
96
0
Order By: Relevance
“…Consistently, our study is supported by previous studies reporting that HIF3A was involved in adipocyte differentiation, insulin resistance, and glucose metabolism (Haertle et al, ), which are key factors contributing to GDM pathogenesis (Davis, Gunderson, Gunderson, Gyllenhammer, & Goran, ). For example, two CpG methylation sites in intron 1 of HIF3A gene, cg16672562, and cg46801562, have significant correlation with obesity (Lee et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistently, our study is supported by previous studies reporting that HIF3A was involved in adipocyte differentiation, insulin resistance, and glucose metabolism (Haertle et al, ), which are key factors contributing to GDM pathogenesis (Davis, Gunderson, Gunderson, Gyllenhammer, & Goran, ). For example, two CpG methylation sites in intron 1 of HIF3A gene, cg16672562, and cg46801562, have significant correlation with obesity (Lee et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, HIF3A expression in subcutaneous adipose tissue was adversely associated with insulin resistance (Main et al, ). In addition, a methylation screening via bisulfite pyrosequencing reported that the average methylation of 11 CpG islands in HIF3A was significantly higher in the blood of GDM patients compared to the controls (Haertle et al, ). Taken together, our data have revealed a role of HIF3A in GDM development, and further study should focus on finding downstream target genes of HIF3A .…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, robust observational data both supporting and refuting an observational link between 1-CM function-through studies on tHcy, folate, or vitamin B 12 and genetic studies, based on either the MTHFR polymorphism alone (44) or a cassette of genetic markers (45)and aberrant metabolic function (46,47), obesity, or type 2 diabetes (48,49). Results from the current study add further evidence to that literature and motivate future functional work on these identified loci that may allow more robust conclusions to be drawn regarding the role of 1-CM function in the etiology of metabolic disease (41,50,51).…”
Section: Dmps In Hif3a Are Associated With Aspects Of Metabolic Syndromementioning
confidence: 56%
“…HIF3A is thought to act as a transcriptional regulator in adaptive response to low-oxygen tension and has a role in glucose, lipid, and amino acid metabolism as well as adipocyte differentiation (37,38). Interestingly, hypermethylation at the HIF3A locus has previously been positively associated with variability in BMI (39), adipose tissue dysfunction (40), and risk of gestational diabetes mellitus (41). There have also been speculations about the role of genetic variants in the PLEKHH2 region as a potential risk factor for diabetic neuropathy (42).…”
Section: Dmps In Hif3a Are Associated With Aspects Of Metabolic Syndromementioning
confidence: 99%
“…Maternal GDM is associated with genome-wide DNA methylation changes in the placenta and cord blood of the exposed offspring 2 . Further studies have revealed that methylation at multiple genes/loci regulated by maternal GDM is responsible for the transmission of GDM effects to the next generation 37 . Another study revealed that GDM has epigenetic effects on genes that are preferentially involved in metabolic disease pathways, with consequences to fetal development 2 .…”
Section: Maternal Factors Affecting Inborn Errors Of Metabolism (Iemsmentioning
confidence: 99%